Pengaruh Pemberian Puding dengan Modifikasi Labu Siam dan Kurma terhadap Kadar Kolesterol Pada Lansia di Puskesmas Suak Tapeh - Meilina, Ayu; Rotua, Manuntun; badaria, Badaria (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2026)
Introduction: Hype.rchole.ste.role.mia is one. of the. non-commu.nicable. dise.ase.s. Hype.rchole.ste.role.mia is characte.rize.d by high le.ve.ls of total chole.ste.rol, LDL, and triglyce.ride.s in the. blood. If not addre.sse.d, this condition can cau.se. chole.ste.rol bu.ildu.p in the. body which le.ads to narrowing of the. coronary arte.rie.s. Objective: To de.te.rmine. the. e.ffe.ct of pu.dding with modifie.d chayote. and date.s on chole.ste.rol le.ve.ls in the. e.lde.rly at Su.ak Tape.h He.alth Ce.nte.r. Methods: This type. of re.se.arch is a qu.asi-e.xpe.rime.nt with a pre.te.st postte.st re.se.arch de.sign with two grou.ps. The. sample. was 60 pe.ople. with chole.ste.rol > 200 mg/dl who we.re. divide.d into two grou.ps, name.ly the. tre.atme.nt grou.p who re.ce.ive.d chayote. and date. pu.dding and the. comparison grou.p who re.ce.ive.d the. original pu.dding u.sing the. random allocation me.thod. Results: The. paire.d sample. t-te.st showe.d a diffe.re.nce. in the. ave.rage. incre.ase. in chole.ste.rol in the. tre.atme.nt grou.p of 13.06 (p-valu.e. = 0.000) and the. comparison grou.p of -7.6 (p-valu.e. = 0.000). While. the. inde.pe.nde.nt sample. t-te.st re.su.lts are. p-valu.e. = 0.000. Conclusion:the.re. is an e.ffe.ct of giving chayote. and date. pu.dding with original pu.dding on change.s in chole.ste.rol in the. e.lde.rly.